Views of Parents on Using Technology-Enhanced Toys in the Free Play of Children Aged One to Four Years - Dimitra Bourha; Maria Hatzigianni; Trifaini Sidiropoulou; Michael Vitoulis (MDPI AG, 2024)
New technology has brought about a novel approach to play termed digital play. Digital play shares many characteristics with traditional play but also presents new possibilities (e.g., building concepts and skills about STEM, opportunities for physical, outdoor activities). Despite new toys with technological characteristics being popular, there is limited research on this specific area for children under four years old and their parents. This study explored parental perspectives and was part of a larger investigation that examined 68 (38 boys and 30 girls) very young children's (1-4 years) engagement with technology-enhanced toys (TETs) in early childhood settings. A sequential explanatory design was employed, wherein parents completed questionnaires before and after their children engaged with TETs. Statistical and thematic analysis revealed that family demographics play an important role in children 's use of TETs and digital technologies (e.g., on the quality of engagement with their children during playing with TETs). Parents noted improvements in their children's skills, including fine motor skills, language, and creativity. This study underscores the importance of considering parental backgrounds in digital technology initiatives for early childhood development. Policymakers and educators may benefit from these insights to tailor digital integration and support children's digital competence effectively.